Modified Gallego’s Stain as Differential Stain for The Assessment of Dentin Morphology - SURESH, CHARANYA; RAMASUBRAMANIAN, DR. ABILASHA (The journal of contemporary issues in business and government, 2020)
Modified Gallego’s stain is a variant of Lille’s stain that uses basic reagents like hematoxylin, carbol fuschin and aniline blue. The study aimed at assessing the efficiency of Modified Gallego’s stain in differentially staining dentin. To check the efficiency of modified Gallego’s stain in differentiating and understanding the histological morphology of dentin, 6 natural teeth (2 posterior teeth and 4 anterior teeth) were chosen using modified Gallego’s stain. Unlike the H & E stain that vaguely stains oral tissues, modified gallego’s stain specifically and differentially stains hard tissue components, especially dentin, which enables easier assessment of dentin morphology. Modified Gallego’s stain is one such stain which not only stains the decalcified sections but also differentially stains the hard tissues of the tooth. When stained with Modified Gallego’s stain, these components were stained with different colours. Hence, it was concluded that Modified Gallego’s stain can be used as a potential tool to stain the hard tissue components of decalcified and ground sections of teeth and can be considered to be used as one of the differential stains for hard tissues especially dentin and as an adjunct to routine H&E.